Acute kidney injury in patients with cancer receiving anti-PD-1/PD-L1 antibodies: incidence, risk factors, and prognosis - Qianqian Lou; Jianguang Gong; Binxian Ye; Rizhen Yu; Shuangshan Bu; Yiwen Li; Bin Zhu; Lina Shao (Renal Failure)
Anti-PD-1/PD-L1 antibodies are widely used in anti-cancer therapy. While they have improved cancer prognoses, immune-related adverse events, which can cause acute kidney injury (AKI), cannot be ignored. The purpose of this retrospective cohort study was to assess the incidence, risk factors, and prognosis of AKI associated with anti-PD-1/PD-L1 antibodies. Patients who received anti-PD-1/PD-L1 antibody treatment at our hospital between January 2018 and December 2022 were enrolled. Clinical information, combined medications, concomitant diseases, tumor types, and laboratory indicators were collected from patient records, and the incidence of AKI was determined. The risk factors for AKI were assessed using univariate and multivariate logistic regression analyses. Overall, 1418 patients were enrolled. The median follow-up time was 112 days and 92 (6.5%) developed AKI. The median time from the initial anti-PD-1/PD-L1 antibody treatment to AKI was 99.85 days. Head and neck cancer and combined use of diuretics, non-steroidal anti-inflammatory drugs (NSAIDs), lower hemoglobin level, and other types of chemotherapeutic drugs were independent risk factors for AKI. The complete recovery, partial recovery, non-recovery, and unknown AKI rates were 7.6%, 28.3%, 52.2%, and 11.9%, respectively. Kidney biopsies were performed on two patients with AKI and pathology confirmed diagnosis of acute tubulointerstitial nephritis. In this cohort, AKI was not uncommon in patients treated with anti-PD-1/PD-L1 antibodies; therefore, it is necessary to monitor renal function and identify AKI early, especially in patients with head and neck tumors. Improving anemia and minimizing the use of diuretics, NSAIDs, and chemotherapeutics may reduce AKI.